Peningkatan Hasil Belajar Menggunakan Model Jigsaw Pada Pembelajaran Tematik Terpadu di Kelas IV Sekolah Dasar - Sagita, Yola; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
The low learning outcomes of teacher-centred learning activities are the impetus for this study. The justification behind this review is to further develop understudy learning results by using the Jigsaw learning model in grade IV. This kind of research employs both qualitative and quantitative approaches. Cycle I had two meetings, whereas Cycle II only had one. The subsequent cycle is utilized to direct research. There are four stages for each cycle: arranging, executing, noticing, and reflecting. Twenty fourth-grade teachers and students served as the study's subjects. The findings revealed that the lesson plans for Cycle I averaged 85% and increased to 92.5 percent for Cycle II. The teacher's assessment of the primary cycle had an average value of 86%, with a 93% increase in the second cycle. While the second pattern's average value was 93 percent, the main pattern's average value was 88.5 percent. In cycle II, student learning outcomes rose from an average score of 74 to an average value of 83. The Jigsaw cooperative student learning model can be interpreted as enhancing learning outcomes.